The Impact of COVID-19 and Exposure to Violent Media Content on Cyber Violence Victimization Among Adolescents in South Korea: National Population-Based Study - Eugene Lee; Peter J Schulz; Hye Eun Lee (JMIR Publications, 2024)
BackgroundBecause of the COVID-19 pandemic and consequent stay-at-home mandates, adolescents faced isolation and a decline in mental health. With increased online activity during this period, concerns arose regarding exposure to violent media content and cyber victimization among adolescents. Yet, the precise influence of pandemic-related measures on experiences of cyber violence remains unclear. Hence, it is pertinent to investigate whether the pandemic altered the dynamics of cyber violence victimization for individuals. ObjectiveThis study aims to investigate the effects of COVID-19 and exposure to violent media content on cyber violence victimization among adolescents in South Korea. MethodsWe used national survey data from 2019 (n=4779) and 2020 (n=4958) to investigate the potential impact of COVID-19 on the prevalence of cyber violence among young adolescents. The data encompassed responses from elementary fourth-grade students to senior high school students, probing their exposure to violent media content, average internet use, as well as experiences of victimization and perpetration. ResultsThe analysis revealed a noteworthy decline in cyber victimization during 2020 compared with 2019 (B=-0.12, t=-3.45, P<.001). Furthermore, being a perpetrator significantly contributed to cyber victimization (B=0.57, t=48.36, P<.001). Additionally, younger adolescents (β=-.06, t=-6.09, P<.001), those spending more time online (β=.18, t=13.83, P<.001), and those exposed to violent media (β=.14, t=13.89, P<.001) were found to be more susceptible to victimization. ConclusionsDespite the widespread belief that cyber violence among adolescents surged during COVID-19 due to increased online activity, the study findings counter this assumption. Surprisingly, COVID-19 did not exacerbate cyber victimization; rather, it decreased it. Given the strong correlation between cyber victimization and offline victimization, our attention should be directed toward implementing real-life interventions aimed at curbing violence originating from in-person violence at school.